Occupation and pregnancy outcome. Issue 8 (August 1987) - McDonald, A D; McDonald, J C; Armstrong, B; Cherry, N; Delorme, C; D-Nolin, A; Robert, D
Abstract : Over a two year period, 1982-4, 56067 women, delivered or treated for a spontaneous abortion in 11 Montreal hospitals covering 90% of such admissions, were interviewed in detail regarding their occupational, social, and personal characteristics in their most recent and past pregnancies–104, 649 in all. These data were analysed in relation to four main adverse outcomes–spontaneous abortion, stillbirth (without defect), congenital defect, and low birth weight (less than or equal to 2500 g). For comparison with observed numbers, expected figures were calculated by logistic regression using up to eight potentially confounding variables. Sixty occupational groups in six main industrial sectors were examined in current and previous pregnancies, with tests for heterogeneity between these two estimates of risk. Women in managerial, health, and clerical sectors had little evidence of excess of any of the four outcomes, by contrast with those in sales, service, and manufacturing sectors. Substantial and statistically significant excesses of spontaneous abortion were observed in nursing aides, women in sales occupations and food and beverage service; of stillbirth in agriculture and horticulture, leatherwork, and certain sales occupations; of congenital defects in women in child care, certain service occupations, and the manufacture of metal and electrical goods; and of low birth weight in chambermaids, cleaners, and janitors, and in women employed in the manufacture of food and drink, metal and electrical goods, and clothing.